PERSEPSI MAHASISWA TENTANG MATERI KULLIAH SEJARAH KONTROVERSIAL PADA PROGRAM STUDI PENDIDIKAN SEJARAH FKIP UNTAN - Filana Sahara; Agus Sastrawan Noor; Ika Rahmatika Chalimi (Universitas Tanjungpura, 2021)
AbstractThis research aims to dertermine the opinion of history education student to controversial historical material in the history education program at the FKIP Tanjungpura University. The method used a survey method with qualitative research. Data collection techniques used indirect communication techniques (questionnaire via Google forms), interview techniques and documents. The sources in this study was representatives of 2016 and 2017 classes history education student who have taken contemporary Indonesian history courses dan lecturer who teach contemporary Indonesian history courses. The result shows that the general student’s perception to controversial historical material are good. It can be seen from each indicators in identification of controversial historical material, lerning process and student’s perception to controversial historical material through the analysis of positive interview results and the average questionnaire results in good categories.Keywords: Controversial Historical, FKIP Untan, Students of Perceptions